MONITORING OF PERIPHERAL VENOUS CATHETERIZATION AT THE SURGICAL HOSPITAL - A. V. Berezhna; S. D. Novikov; T. O. Chumachenko (Eastern Ukrainian Medical Journal, 2020)
Introduction. Peripheral venous catheters are widely used in medical practice to provide continuous venous access for therapeutic and diagnostic purposes. Peripheral vascular catheterization can be accompanied by infectious complications, including catheter-related bloodstream infections. An effective system of epidemiological surveillance and infection control of catheter-related bloodstream infections has not been developed at the state level in Ukraine; there is no proper monitoring for administration site and no registration of complications associated with the vascular catheterization. The purpose of this work was to assess the validity and propriety of the use of peripheral venous catheters in patients who receive inpatient treatment.Materials and methods. Between October 2019 and April 2020, 93 adult patients who were peripheral venous catheterized in a surgical hospital in Kharkiv were included in a prospective epidemiological study. The author's observation card was used for data collection for each patient daily. The catheter site was observed daily, and the following symptoms were entered into the card: flushed skin, swelling, discharge, and pain at the administration site at rest and on palpation. Interpretation of symptoms was conducted using the visual infusion phlebitis scale by A. Jackson. Statistical processing of data was carried out using descriptive statistics methods. To identify the relationship between the nominative values, Pearson's criterion χ2 was determined with P < 0.01.Research results. 51 women (54.8%) and 42 men (45.2%) aged 18 to 84 were enrolled. In total, patients spent 619 bed-days in the hospital, of which the proportion of days with vascular catheters equaled 90.8% (n = 562). The main indication for the catheterization procedure was multicomponent therapy or the use of incompatible medications (98.9% / n = 92). In total, 148 peripheral venous catheters were inserted in these patients. The number of vascular catheters per patient ranged 1 to 3. According to the data of daily monitoring of the administration site, the signs of inflammation were observed in 65.5% of cases (n = 97). The incidence of signs of inflammation at the administration site with the first catheterization was significantly higher (χ2 = 25.2804; p < 0.00001) than that with the second or third catheterization. The signs of local inflammation, which were more common in patients with vascular catheters, included flushed skin in the area of the catheter site (65.5% / n = 97), complaints of pain on palpation in the area of the catheter site (60.8% / n = 90) and swelling in the area of the catheter site (57.4% / n = 85). It was found that for more than half of the cases (55.4% / n = 82), the patients had symptoms of middle-stage phlebitis. It was also revealed that the most common reason for the removal of a peripheral venous catheter (n = 148) in the studied hospital were signs of local inflammation at the catheter site (61.5% / n = 91). However, in 16.9% of cases (n = 25), the occurrence of at least two signs of local inflammation at the catheter site, which indicated the initial stage of phlebitis and required to rearrange the catheter, was not the reason for immediate catheter removal.Conclusions. Health care workers make mistakes when working with peripheral venous catheters; in particular, there is no timely replacement of vascular catheters in the event of signs of infusion phlebitis. To reduce the risk of infectious complications of vascular catheterization at a health facility, the indications for insertion and removal of peripheral venous catheters and central venous catheters should be clearly defined, and standard operating procedures for ensuring vascular access and algorithms for managing patients with vascular catheters should be developed and implemented.